PENGARUH EMPLOYER BRANDING DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP RETENSI KARYAWAN GENERASI Z DI BEKASI - Firly Agustiansyah; Umban Adi Jaya; Riani Winarni; Tri Sanatha Wahyu Akbar; Mawih (Universitas Sains Indonesia Publishing, 2025)
This study aims to analyze the effect of Employer Branding and Transformational Leadership on Generation Z Employee Retention in Bekasi. The study uses a quantitative method with an associative approach and involves 100 Generation Z respondents working in Bekasi. Data collection was conducted using a five-point Likert scale questionnaire. The results show that all instruments are valid and reliable. Classical assumption tests also prove that the data are normally distributed and free from multicollinearity and heteroscedasticity. Multiple linear regression results show that Employer Branding and Transformational Leadership have a positive and significant effect on Employee Retention, both partially and simultaneously. The R Square value of 0.842 indicates that 84.2% of the changes in Employee Retention are explained by these two variables. This finding confirms that a positive company image and an inspirational leadership style are important factors in increasing Generation Z's decision to stay working at the company.